Relieving your stress: PGPB associated with Andean xerophytic plants are most abundant and active on the most extreme slopes - Aguilera-Torres, Carla; Riveros, Gustavo; Morales, Loreto V.; Sierra-Almeida, Angela; Schoebitz, Mauricio; Hasbún, Rodrigo (Frontiers in Microbiology, 2023)
Plants interact with plant growth-promoting bacteria (PGPB), especially under stress condition in natural and agricultural systems. Although a potentially beneficial microbiome has been found associated to plants from alpine systems, this plant-PGPB interaction has been scarcely studied. Nevados de Chillán Complex hold one of the southernmost xerophytic formations in Chile. Plant species living there have to cope with drought and extreme temperatures during the growing season period, microclimatic conditions that become harsher on equatorial than polar slopes, and where the interaction with PGPB could be key for plant survival. Our goal was to study the abundance and activity of different PGPB associated to two abundant plant species of Andean xerophytic formations on contrasting slopes. For this, twenty individuals of Berberis empetrifolia and Azorella prolifera shrubs were selected growing on a north and south slope nearby Las Fumarolas, at 2,050 m elevation. On each slope, microclimate based on temperature and moisture conditions were monitored throughout the growing period. Chemical properties of the soil under plant species canopies were also characterized. Bacterial abundance was measured as Log CFU g-1 from soil samples collected from each individual and slope. Then, the most abundant bacterial colonies were selected, and different hormonal (indoleacetic acid) and enzymatic (nitrogenase, phosphatase, ACC-deaminase) mechanisms that promote plant growth were assessed and measured. Extreme temperatures were observed in the north facing slope, recording the hottest days (41 vs. 36ºC) and coldest nights (-9.9 vs. 6.6ºC). Moreover, air and soil moisture were lower on north than on south slope, especially late in the growing season. We found that bacterial abundance was higher in soils on north than on south slope but only under B. empetrifolia canopy. Moreover, the activity of plant growth-promoting mechanisms varied between slopes, being on average higher on north than on south slope, but with plant species-dependent trends. Our work showed how the environmental heterogeneity at microscale in alpine systems underlies variations in the abundance and plant growth promoting activity of the microorganisms present under the plant canopy of the Andean xerophytic formations and highlight the importance of PGPB from harsh systems as biotechnological tools for restoration.